Knowledge of Pregnant Before and After Educational Module on Postpartum Family Planning - Ernawati; Sumarmi; Nuryana, Riska; Kartini, Anita; Nurftariwi, Indriani (Omni Nursing Journal, 2024)
Background: Integrating modern contraceptive education during antenatal care is essential to promote the uptake of postpartum family planning (PPFP), potentially reducing the risk of unintended pregnancies and closely spaced births. Objective: This study aimed to assess the knowledge of third-trimester pregnant women before and after receiving an educational module on PPFP in the working area of the Mangarabombang Health Center, Takalar Regency. Methods: This primary study employed a descriptive quantitative design with a pre-post approach. A total of 62 third-trimester pregnant women were selected through total sampling. A structured questionnaire was used to measure knowledge before and after intervention, with validity and reliability confirmed in prior studies. Results: Prior to the intervention, 70.96% of respondents had poor knowledge, 19.35% moderate, and 9.67% good. After receiving the educational module, 43.54% had good knowledge, 50% moderate, and 6.45% poor. Improvements were noted across age, education level, and parity groups. Conclusion: Educational modules effectively improved PPFP knowledge among pregnant women. However, older mothers, those with lower education, and higher parity tended to retain lower knowledge levels. It is recommended to provide targeted counseling for these groups.